Poly (Butylene Adipate‐Co‐Terephthalate) (PBAT) – Based Biocomposites: A Comprehensive Review - Blessing E. Itabana; Amar K. Mohanty; Phil Dick; Mohini Sain; Atul Bali; Mike Tiessen; Loong‐Tak Lim; Manjusri Misra (Macromolecular Materials and Engineering)
Abstract With the issue of plastic waste persisting and the need for more sustainable solutions to the ever‐increasing demand for lightweight and durable plastic products, this review has become imminent and compelling. Poly (butylene adipate‐co‐terephthalate) (PBAT) is a biodegradable polymer with exceptional film‐forming ability resembling those of low‐density polyethylene. PBAT has a huge advantage for packaging applications due to its remarkably high elongation at break, giving it a good processing window for its application in packaging. However, certain defiant intrinsic properties stand in the way of its full commercialization. The development of blends and biocomposites of PBAT has, therefore, become imperative for complementing its properties and producing a superior material. This paper focuses on the recent developments in preparing PBAT‐based blends and biocomposites with superior mechanical, barrier, and antimicrobial properties and, most importantly, has also investigated how the development of these blends and biocomposites impacts the biodegradation rate of PBAT. It also highlights the possible synthesis of bio‐based PBAT and the commercialization, market trends, and prospects of PBAT‐based materials for flexible, rigid packaging, and other industrial applications compared with biodegradable alternatives.